Perhitungan pajak penghasilan pasal 25 atas badan: Studi kasus pada PT Blue Bird Tbk - Kamalia, Isna; Ramadhani, Sri Wahyu; Styawati, Diyah Ajeng; Aprilian, Rifky Zahrul; Arnanda, Putri Amalia (Maliki Interdisciplinary Journal, 2024)
This research is a mechanism for calculating Income Tax (PPh) Article 25 at PT Blue Bird Tbk and confirms that the company has carried out calculations in accordance with applicable tax provisions. The type of research used in this research is qualitative research and the data used in this research is secondary data and is of the qualitative type (qualitative data). Through in-depth analysis of company tax data, it was found that there were no significant differences in the calculation of PPh Article 25 between those carried out by the company and the applicable tax provisions. These results show the consistency, accuracy and high satisfaction of PT Blue Bird Tbk with existing tax regulations.